Hepatic Veno-Occlusive Disease caused by Gynura Segetum: A Case Report - Ya, Li; Yulin, Ma; Jialing, Li; Jing, Wan (Cardiology and Cardiovascular Medicine, 2019)
Objective: To analyze the clinical characteristics of Hepatic venous-occlusive disease induced by Gynura segetum. Methods: The process of diagnosis and treatment of the patient with Hepatic venous-occlusive disease who are admitted to Zhongnan hospital. Results: The patient has the following clinical features: he is an old man who has a history of taking Gynura segetum and has abdominal distension, abdominal pain, and ascites. We can diagnosis with the medical history and the auxiliary examination. Conclusions: Gynura segetum is an important predisposing factor for Hepatic veno-occlusive disease. The clinical manifestations are mainly liver dysfunction and abnormal coagulation function. A detailed medical history and early diagnosis and treatment can contribute to a good prognosis during the clinical work, we should be aware of the correct use of Gynura segetum.